Sex-specific associations of serum testosterone with gray matter volume and cerebral blood flow in midlife individuals at risk for Alzheimer’s disease - Matilde Nerattini; Schantel Williams; Caroline Andy; Caroline Carlton; Camila Zarate; Camila Boneu; Francesca Fauci; Trisha Ajila; Steven Jett; Michael Battista; Silky Pahlajani; Valentina Berti; et al. (PLoS ONE, 2025)
Testosterone, an essential sex steroid hormone, influences brain health by impacting neurophysiology and neuropathology throughout the lifespan in both genders. However, human research in this area is limited, particularly in women. This study examines the associations between testosterone levels, gray matter volume (GMV) and cerebral blood flow (CBF) in midlife individuals at risk for Alzheimer’s disease (AD), according to sex and menopausal status. A cohort of 294 cognitively normal midlife participants, 83% female, ages 35–65 years, with an AD family history and/or Apolipoprotein E epsilon 4 (APOE-4) genotype, underwent volumetric Magnetic Resonance Imaging (MRI) to measure GMV and MR-Arterial Spin Labeling (ASL) for measurement of CBF. We used voxel-based analysis and volumes of interest to test for associations between testosterone (both total and free testosterone) and brain imaging outcomes, stratified by sex and menopausal status. Higher total and free testosterone levels were associated with larger GMV in men, with peak effects in frontal and temporal regions. Conversely, in women, higher testosterone levels correlated with higher CBF, with peak effects in frontal and limbic regions, subcortical areas and hypothalamus. Among women, associations between testosterone and GMV were observed at the premenopausal and perimenopausal stages, but not postmenopause, whereas associations of testosterone with CBF were significant starting at the perimenopausal stage and were more pronounced among hormone therapy non-users. Results were independent of age, APOE-4 status, midlife health indicators, and sex hormone-binding globulin levels. These findings indicate sex-specific neurophysiological effects of testosterone in AD-vulnerable regions in midlife individuals at risk for AD, with variations observed across sex and menopausal status. This underscores the need for further research focusing on the neuroprotective potential of testosterone in both sexes.